Bivalves from the latest Jurassic-earliest Cretaceous hydrocarbon seep carbonates from central Spitsbergen, Svalbard - Hryniewicz, Krzysztof; Little, Crispin T.s.; Nakrem, Hans Arne (Zootaxa, 2014)
The bivalve fauna from the latest Jurassic–earliest Cretaceous hydrocarbon seep deposits from central Spitsbergen, Svalbard comprises at least 17 species, four of which belong to chemosymbiotic taxa often found at seeps. These are the solemyid Solemya (Petrasma) cf. woodwardiana; Nucinella svalbardensis sp. nov., which belongs to a group of large Nucinella species known from seeps and deep water environments; the lucinid bivalve, Tehamatea rasmusseni sp. nov., included in a genus widely distributed in other Jurassic–Cretaceous seeps; and Cretaxinus hurumi gen. et sp. nov., which is the oldest known thyasirid and is discussed in relation to other large seep-restricted genera in this family. The remaining species in the fauna belong to ‘background’ genera known from coeval normal marine sediments, mostly from the Boreal area. These include the nuculid Dacromya chetaensis, two new malletiids (Mesosaccella rogovi sp. nov. and M. toddi sp. nov.), the oxytomiid Oxytoma octavia, at least three Buchia species, at least two pectinids, including Camptonectes (Costicamptonectes) aff. milnelandensis and Camptonectes (Camptochlamys) clatrathus, the limid Pseudolimea arctica, the arcticid Pseudotrapezium aff. groenlandicum, and the pholadomyid Goniomya literata. The large number of ‘background’ species in the bivalve fauna is probably a reflection of the shallow-water setting of the Svalbard seeps. This might also explain the lack of the seep-restricted modiomorphid bivalve Caspiconcha from the fauna. With solemyids, Nucinella, lucinids and thyasirids, the latest Jurassic–earliest Cretaceous bivalve seep fauna of Svalbard contains typical representatives of the Mesozoic bivalve seep faunas, both long established and young evolutionary colonists.